Efficacy of Extracts of African Eggplant and Okra Leaves on Alloxan-Induced Diabetes Mellitus Adult Male Albino Rats - Onuora, Ethel E.O.; Okafor, Christiana N. (Pakistan Journal of Nutrition, 2016)
Diabetes mellitus is one of the major disease that is common among many communities in Nigeria. Among the two types of diabetes mellitus (Types 1 and 2), type 2 is the most common. There is tendency for its increase due to genetic, environmental factors such as obesity, increasing number of elderly people and lack of exercise. Drugs for treatment of diseases are expensive for the low income groups in Nigeria. Plants have medicinal, food and economic values. Herbal medicine is the mainstay for about 75 to 80% of the low income groups to treat diabetes mellitus. This is due to better cultural acceptability and compatibility with the human body and minimum side-effects. This study evaluated the efficacy of extracts of African eggplant (Solanum macrocarpon L.) and okra (Abelmoschus esculentus L.) leaves on alloxan induced diabetic adult male albino rats. The extracts were able to tremendously lower the high blood glucose levels of the diabetic rats to normal. The rats fed with 300 mg level of leaf extract of A. esculentus had the highest decrease when compared with others. The total cholesterol, high and low density cholesterol and triglycerides values of the rats were also lowered by the two extracts.